PENURUNAN KADAR AMONIA FESES AYAM PEDAGING MENGGUNAKAN PREBIOTIK BUNGKIL INTI SAWIT DENGAN INOKULUM BAKTERI Lactobacillus acidophilus, Lactobacillus bulgaricus, DAN Bacillus cereus - Ridho Mathori Ikhwan; MG. Isworo Rukmi; Sri pujiyanto (Jurnal Akademika Biologi, 2016)
Ammonia emissions at the farm that was from the broiler faecal waste inflict restlessness and become the source of respiratory diseases to the local people because the farm is located adjacent to residential areas. Bacterial isolates were characterized as acid producer with BIS prebiotic mixture may be a bioremediation agent to reduce ammonia emissions in broiler feces. The purpose of this research is to create a biotechnology product which is ready to apply for reducing the ammonia at the poultry farm.  As the treatment used three isolates of bacteria such as L. acidophilus, L. bulgaricus and B. cereus were each used to ferment the BIS for 48 hours at a temperature of 38 ° C. Results of subsequent fermentation inoculated into the stool with a concentration of 8% (w / w), and incubated for 48 hours. Observations ammonia, pH and microflora in the stool, were done at 24 and 48 h of incubation. The results showed a decrease in the levels of ammonia and pH were significantly different between the control and all treatments, but there is no real difference between each treatment of bacterial isolates. Decreased levels of ammonia at 24 h incubation by L. acidophilus, L. bulgaricus and B. cereus, respectively for 92.89%, 98.78%, 98.56%, while the 48-hour incubation, respectively for 90.67 %, 89.60% and 96.80%.Keywords; Ammonia, Acid Producing Bacteria, Prebiotics, BIS, Broiler